The Influence of Topography on Structural Dynamics in River-Adjacent Areas: A Study of Soil-Structure Interaction - Gaye, Daouda; Hassan Mohamed, Hassan Omer; Serigne Saliou, Sene (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2025)
This study investigates the impact of topography on the structural dynamics of buildings located near rivers, focusing on Soil-Structure Interaction (SSI). Through a combination of geotechnical data analysis, finite element modeling, and hydrological measurements, the study evaluates the stability and performance of structures in river-adjacent environments during dynamic events such as seismic activity and floods. The results show that buildings located near riverbanks or on sloped terrain experience greater settlement and lateral displacement compared to inland structures. Additionally, the study highlights the risks of soil liquefaction and foundation instability in saturated soils during seismic events. Engineering recommendations include adaptive foundation designs, erosion control measures, and continuous monitoring to enhance the resilience of structures in river-adjacent areas.